Utilising grape juice processing by-products as bulking and colouring agent in white chocolate - Altinok, Emir; Kurultay, Sefik; Konar, Nevzat; Toker, Omer Said; Kopuk, Berkay; Gunes, Recep; Palabiyik, Ibrahim (OXFORD UNIV PRESS, 2022)
In this study, grape pomace (mixture of grape seeds and skins) powder (GPP), obtained from grape processing, was used at different concentrations [10.0 (GPP10), 20.0 (GPP10) and 30.0 (GPP10) g/100 g] in white chocolate formulation for the partial replacement of sucrose. The results indicated that GPP addition at a higher concentration (>10.0 g/100 g) significantly affected the particle size, moisture content, texture and flow behaviour of white chocolate samples (P < 0.05). However, using GPP at a concentration of 10.0 g/100 g had advantages for physicochemical and flow properties. As expected, under simulated in vitro digestion conditions, the bioaccessibility of total phenolic compounds in saliva, gastric juice and intestinal juice for GPP10 samples was significantly higher than the control (P < 0.05). In conclusion, results of the study showed that it was possible to partially replace the sucrose with GPP at a concentration of 10.0 g/100 g in white chocolate formulations.
Keywords: Bioaccessibility; grape pomace; texture; white chocolate; PARTICLE-SIZE DISTRIBUTION; PHYSICAL-PROPERTIES; RHEOLOGICAL PROPERTIES; MILK CHOCOLATE; DIETARY FIBER; POLYPHENOLS; SWEETENERS; QUALITY; INULIN; DARK; Food Science & Technology